Familial Atypical Hemolytic Uremic Syndrome with Positive p.S1191L (c.3572C>T) Mutation on the CFH Gene: A Single-center Experience - Dursun, Ersoy F.; Yesil, G.; YEŞİL, GÖZDE; Sasak, G.; Dursin, H. (My University, 2021)
The atypical hemolytic uremic syndrome (aHUS) is characterized by thrombocytopenia, microangiopathic hemolytic anemia and acute kidney injury (AKI), which can exhibit a poor prognosis. Complement factor H (CFH) gene mutations play a key role in this disease, which may be sporadic or familial. We studied 13 people from the same family, investigated for gene mutations of the familial aHUS after a family member presented to our emergency clinic with the aHUS and reported a family history of chronic renal failure. The p.S1191L mutation on the CFH gene was heterozygous in six people from the patient-s family with the aHUS. One of these family members is our patient with acute kidney injury, and the other two are followed at the Nephrology Clinic, Medeniyat University, Goztepe Training and Research Hospital, Istanbul, Turkey, due to chronic renal failure. The other three family members showed no evidence of renal failure. The index case had a history of six sibling deaths; three died of chronic renal failure. Plasmapheresis and fresh frozen plasma treatment were administered to our patient. When the patient showed no response to this treatment, eculizumab (ECZ) therapy was started. The study demonstrated that thorough family history should be taken in patients with the aHUS. These patients may have the familial type of the disease, and they should be screened genetically. Eculizumab should be the first choice in the treatment with plasmapheresis. It should be kept in mind that the use of ECZ as prophylaxis in posttransplant therapy is extremely important for preventing rejection.
Keywords: Complement factor H (CFH) gene; Eculizumab (ECZ); Familial atypical hemolytic uremic syndrome (aHUS); Plasmapheresis; p.S1191L mutation